The Effects of Halal Certification and Web Design on Purchase Intention Mediated by Brand Trust in E-Commerce of Halal Cosmetics Consumers in Bandung Raya - Hariyadi Triwahyu Putra; Desi Riyanti; Dita Anggraeni (Ilomata International Journal of Management, 2023)
The purpose of this study is to analyze the effects of halal certification and web design on purchase intention mediated by brand trust in e-commerce of halal cosmetic consumers in Bandung Raya. The novelty of the research is the combination of the independent variables namely halal certification and web design taken from the previous research, with the Greater Bandung area as the research location. The instrument used as the data collection tool comprising 123 respondents who are the consumers of halal cosmetics, aged 15 to 64 to be assessed in this study. The technique of determining the sample, the number of samples and the data analysis techniques can be adjusted to the object of research conducted for further researches. The analytical tools to test the instrument data are validity and reliability tests, classical assumption tests and Sobel tests with SPSS version 25 software tools. Of the 7 proposed research hypotheses, 6 hypotheses are supported by empirical data. The results of this study can also be useful for object managers who are assessed regarding the design of strategies or programs that are relevant to improve the quality of these attributes.